CREATING HUMAN RESOURCES INDUSTRIES COMPETITIVENESS WITH RESOURCES SHARING INNOVATION MODEL - Syamsul Hidayat; Bambang Dwi Suseno; Furtasan Ali Yusuf; Dewi Surani (International Interdisciplinary Conference on Sustainable Development Goals, 2020)
A paradoxical condition existence in which regions with abundant number of manufacturing companies have high unemployment rates, so it is interesting and important to research in order to find answers to provide innovative and sustainable policy mix recommendations for local governments. This research will offer a breakthrough in the form of resource sharing innovation between manufacturing companies and training institutions. Then the research stages are: (1) Mapping Unemployment, (2) Data and Information Collection, (3) Data Management and Presentation in the form of a research model, (4) Focus Group Discussion, (5) Training, (6) Recommendations, (7) Scientific Publications. This study uses a Research and Development (R & D) procedure with the target of formulating a model of unemployment socio-economic conditions that causes poverty in industrial areas and a resource sharing model. This research is useful to assist the government in helping alleviate unemployment. The results of this research will be made recommendations and scientific publications in the form of international journals and conferences. The results of this study indicate that Resource Sharing Innovation (RSI) has an effect on Industrial Competitiveness of 0.247, CR value of 2.839 and p-value of 0.005. Based on these results, it can be concluded that it is proven that Enjoyment of developing talent has a significant positive effect on Industrial Competitiveness at the 5% significance level. Furthermore, the discussion is further explained in this study.